Groundwater level prediction using machine learning algorithms in a drought-prone area - Pham Q.B.; Kumar M.; Di Nunno F.; Elbeltagi A.; Granata F.; Islam A.R.M.T.; Talukdar S.; Nguyen X.C.; Ahmed A.N.; Anh D.T. (Springer Science and Business Media Deutschland GmbH, 2023)
Crops; Cultivation; Decision trees; Errors; Forecasting; Groundwater resources; Learning algorithms; Mean square error; Statistical tests; Support vector machines; Absolute error; Bangladesh; Correlation coefficient; Ground water level; Groundwater prediction; Locally weighted linear regression; Mean absolute error; Random tree; Root mean square errors; Squared errors; Groundwater